Temporal and spatial development of serotonin and dopamine neurons in the Drosophila CNS. - Lundell, M.J.; Hirsh, J. (Developmental Biology, 1994)
We present a high-resolution profile of the temporal and spatial immunoreactivity for dopamine and serotonin in the Drosophila embryonic CNS and the expression pattern of two enzymes important in their biosynthesis, DOPA decarboxylase (DDC) and tyrosine hydroxylase (TH). DDC performs the final catalytic step in the synthesis of both biogenic amines and TH is the rate-limiting enzymatic step in the synthesis of dopamine. We show that the DDC-expressing neurons synthesize either serotonin or dopamine, but not both, and that the two neuronal subtypes follow similar axonal pathways. In addition, we describe two DDC-expressing cell types that do not synthesize detectable levels of serotonin or dopamine. We also describe a novel set of TH-expressing neurons that are detected only during embryogenesis. The initial appearance of both enzymes and their metabolites during embryogenesis shows unexpected diversity. The onset of Ddc expression is heterogeneous, such that certain classes of cells express high levels of DDC several hours before others. High levels of TH immunoreactivity are observed at a time when DDC immunoreactivity is barely detectable. Despite low levels of DDC, both dopamine and serotonin are first detected at the earliest stages of DDC expression. We discuss the implications of these observations in the differentiation of dopamine and serotonin neurons.